Proteomics‐based identification of the role of osteosarcoma amplified‐9 in hepatocellular carcinoma recurrence. Issue 8 (16th April 2022) - Wei, Xuyong; Yang, Mengfan; Pan, Binhua; Zhang, Xiaobing; Lin, Hanchao; Li, Wangyao; Shu, Wenzhi; Wang, Kun; Khan, Abdul Rehman; Zhang, Xuanyu; Cen, Beini; Xu, Xiao
Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies; its recurrence is associated with high mortality and poor recurrence‐free survival and is affected by multisystem and multilevel pathological changes. To identify the key proteins associated with tumor recurrence and the underlying mechanisms, proteomic profiling of tumor specimens from early recurrence and nonrecurrence patients was performed in this study. Proteomics was applied to identify differentially expressed proteins during the early recurrence of HCC after surgery. Osteosarcoma amplified‐9 (OS‐9) was discovered, and the correlation between OS‐9 expression and the clinicopathological characteristics of patients was analyzed. Invasion and migration were examined in SMMC‐7721 cells with and without OS‐9 overexpression. Proteomics was performed once again using SMMC‐7721 cells with OS‐9 overexpression to further analyze the proteins with altered expression. OS‐9 was overexpressed in the early recurrence group, and OS‐9 overexpression was associated with high serum alpha‐fetoprotein levels and poor recurrence‐free survival in 196 patients with HCC. The invasion and migration abilities of SMMC‐7721 cells were enhanced in the OS‐9 overexpression group. Bioinformatic functional enrichment methods, including Gene Ontology annotation and Kyoto Encyclopedia of Genes and Genomes pathway analysis, revealed that the hypoxia‐inducible factor 1 (HIF‐1) and tumor necrosis factor (TNF) signaling pathways were activated in the OS‐9 overexpression group. The migration and invasion capacities of OS‐9 overexpressed HCC cell line were weakened while treated with HIF‐1α or TNF‐α inhibitors. Conclusion: Our results suggest that the overexpression of OS‐9 is related to HCC recurrence, thereby contributing to the migration and invasion capacities of HCC cell line by regulating the HIF‐1 and TNF pathways. Abstract : Proteomics was applied to discover the differentially expressed proteins in the early recurrence of patients with HCC after surgery. Osteosarcoma amplified‐9 (OS‐9) was discovered to be overexpressed in the early recurrence group, which also manifested the relationship with serum AFP levels and recurrence‐free survival in 196 patients. Bioinformatics functional enrichment methods including GO annotation and KEGG pathway analysis revealed that the HIF‐1 signaling pathway and TNF signaling pathway were activated in the OS‐9 overexpression group.image